Implementation of a project-based worksheet using Aloe vera gel as a natural stabilizer in purple sweet potato ice cream to increase nutritional literacy - Sari Sari; Sylvania Wiendhy; Saepudin Rahmatullah; Brilliant Dwi Izzulhaq; Rizqy Nur Sholihat (EDUSAINS, 2025)
This study was motivated by the low level of nutritional literacy among students in obtaining, processing, and understanding information to make appropriate decisions regarding nutritional choices. The purpose of this study was to examine students' learning activities in analyzing nutritional literacy through the application of project-based worksheets, as well as to analyze the characteristics of purple sweet potato ice cream. The method used was a pre-experimental design with a one-group pretest-posttest design, involving 35 students from one school in Indonesia. The results showed that students' learning activities were very good, with an engagement rate of 88%. Students' nutritional literacy improved significantly, with an N-Gain value of 0.50, which falls into the moderate category. Additionally, the physical characteristics of purple sweet potato ice cream using aloe vera gel stabilizer and CMC met the standards of SNI No. 01-3713-1995. This study contributes to contextual science learning through the development of project-based worksheets that not only enhance students' nutritional literacy but also connect scientific knowledge with real-world practice through simple experimental activities.